ChemInform Abstract: Conjugated Oligomers and Polymers Sheathed with Designer Side Chains. Issue 43 (October 2015) - Pan, Chengjun; Zhao, Chunhui; Takeuchi, Masayuki; Sugiyasu, Kazunori
Abstract Review: [molecular design of insulated molecular wires and their unique photophysical, electronic, and mechanical properties; 70 refs.